If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 6y + 62 + -6x + 6y + -18 = 0 Reorder the terms: 62 + -18 + 4x + -6x + 6y + 6y = 0 Combine like terms: 62 + -18 = 44 44 + 4x + -6x + 6y + 6y = 0 Combine like terms: 4x + -6x = -2x 44 + -2x + 6y + 6y = 0 Combine like terms: 6y + 6y = 12y 44 + -2x + 12y = 0 Solving 44 + -2x + 12y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-44' to each side of the equation. 44 + -2x + -44 + 12y = 0 + -44 Reorder the terms: 44 + -44 + -2x + 12y = 0 + -44 Combine like terms: 44 + -44 = 0 0 + -2x + 12y = 0 + -44 -2x + 12y = 0 + -44 Combine like terms: 0 + -44 = -44 -2x + 12y = -44 Add '-12y' to each side of the equation. -2x + 12y + -12y = -44 + -12y Combine like terms: 12y + -12y = 0 -2x + 0 = -44 + -12y -2x = -44 + -12y Divide each side by '-2'. x = 22 + 6y Simplifying x = 22 + 6y
| -9(0.25)+6-(0.25)=4 | | -y-[6(y-1)-2(3+y)]=3(4-y)-2y | | 92-14=-45 | | 17=4y+8-7y | | 2x+3.6=x+2.8 | | 0.3x+21=-0.7x+8 | | 24x^2y-42xy+9y=0 | | 11x+-6=17 | | x^2-12+36=4 | | x^2+5x+125=0 | | -3x-7=4x-35 | | 4x^2+5x+125=0 | | 2c^2+9cw-35w^2=0 | | 40w^3+36w^2+8w=0 | | 5x-3-2x=4x+7 | | 4x-11=3x+11 | | (4p-3q)(9p+2q)=36p^2-19pq-6q^2 | | 8x^3+6x^2-9x=0 | | 3x+8x=22 | | 3m+3=3 | | 30z^2-35z+10=0 | | 1.5s-1.2-s=.5 | | 2q^2+11qd-63d^2=0 | | 12(2x-6)=3(8x+3) | | (x-9)(x-9)=10 | | 5r-4r-6=-7 | | 12(2x-6)=(8x+3) | | 16=3w/5 | | 11-x= | | 5z^2+32z-21=0 | | 8=3k+5-3k | | (x-9)(x-9)=x-11 |